Political Communication Strategy H. Sumaryo, BA as a Legislative Member Candidate in the 2019 General Election in Siak Regency - Abdullah Mitrin; Tania Dwika Putri (Formosa Journal of Multidisciplinary Research, 2022)
Political communication is a communication medium that can be used by candidates for legislative members to their prospective voters. This is considered as an information distribution system that can facilitate access to information by voters to legislative candidates. So that voters in choosing their representatives will be based more on track record information and work programs. This research uses a descriptive qualitative approach using the case study method. To find out in depth about the problems being studied, this study used a key informant, namely H. Sumaryo BA as a candidate for legislative members in the 2019 elections in Siak Regency. The results of the study stated that the political communication strategy carried out by H. Sumaryo BA as a legislative member candidate in the 2019 general election in Siak Regency was a positioning strategy (strengthening strategy, persuasion strategy) which was modified with a political communication strategy which included maintaining institutional strengthening character, understanding the audience , crafting persuasive messages, setting methods, choosing media, the art of compromise and being willing to open up. This research concludes that the more dominant and effective strategy used in the winning strategy in the 2019 legislative elections by H.Sumaryo BA is the Caring for Character strategy.